Perilaku Masyarakat dalam Pemanfaatan Pekarangan Rumah dalam Rangka Mewujudkan Kemandirian Pangan Keluarga di Desa Wakorambu Kabupaten Muna - La Ode Dwiyan Pramono Darmin; La Parasit; Jasir. B Jasir. B; Ilham Ilham (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2025)
This study describes the community's behavior in utilizing home yards to achieve family food self-sufficiency in Wakorambu Village, Muna Regency. The objective is to analyze the behavior of the Wakorambu Village community in utilizing home yards as productive land. The research employs a qualitative method with a descriptive analysis model. Data were collected through in-depth interviews, observation, and documentation. The study results show that the behavior of the community in utilizing home yards is influenced by three main factors: (1) adequate yard size, allowing the community to grow various types of plants; (2) soil fertility that supports plant growth without requiring significant additional fertilizers, and (3) active use of home yards, ensuring the land is not left idle. Residents who utilize their home yards significantly improve their family income. The study recommends that communities who have not yet utilized their home yards should start managing them optimally to gain more significant economic and environmental benefits.